Promoting Inclusion Oral-Health: Social Interventions to Reduce Oral Health Inequities - Freeman , Ruth E. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The aim of this collection of papers is to provide the reader with a cogent understanding of the role of evidence in the development of social or community-based interventions to promote inclusion oral-health and reduce oral health, health, and psychosocial inequities. In addition, this material will include various methods used for their implementation and evaluation. At the outset, the reader will be offered a working definition of inclusion oral-health, which will be modelled on the work of Luchenski et al. [1]. The interventions described are theoretically underpinned by a pluralistic definition of evidence-based practice [2] and the radical discourse of health promotion as postulated by Laverack and Labonte [3] and others [4,5]. This Special Issue will consist of eight papers, including an introduction. The first three papers will examine the various sources of evidence used to transform top-down into bottom-up community-based interventions for people experiencing homelessness; people in custody and for families residing in areas of high social deprivation. The final four papers will report on the implementation and evaluation of social or community-based interventions. This collection of research papers will highlight the importance of focusing on prevention and the adoption of a common risk factor agenda to tackle oral health, health and psychosocial inequities felt by those most excluded in our societies.